Predicting progression to dementia in persons with mild cognitive impairment using cerebrospinal fluid markers. Issue 8 (16th February 2017) - Handels, Ron L.H.; Vos, Stephanie J.B.; Kramberger, Milica G.; Jelic, Vesna; Blennow, Kaj; van Buchem, Mark; van der Flier, Wiesje; Freund‐Levi, Yvonne; Hampel, Harald; Olde Rikkert, Marcel; Oleksik, Ania; Pirtosek, Zvezdan; et al.
Abstract: Introduction: We aimed to determine the added value of cerebrospinal fluid (CSF) to clinical and imaging tests to predict progression from mild cognitive impairment (MCI) to any type of dementia. Methods: The risk of progression to dementia was estimated using two logistic regression models based on 250 MCI participants: the first included standard clinical measures (demographic, clinical, and imaging test information) without CSF biomarkers, and the second included standard clinical measures with CSF biomarkers. Results: Adding CSF improved predictive accuracy with 0.11 (scale from 0–1). Of all participants, 136 (54%) had a change in risk score of 0.10 or higher (which was considered clinically relevant), of whom in 101, it was in agreement with their dementia status at follow‐up. Discussion: An individual person's risk of progression from MCI to dementia can be improved by relying on CSF biomarkers in addition to recommended clinical and imaging tests for usual care.